Development of Mathematics Learning Media Using Kvisoft Flipbook Application for Linear Programming Material - Resdiana Safithri (Universitas Teknokrat Indonesia, 2026)
This research aims to produce valid and practical mathematics learning media using the Kvisoft flipbook application for linear programming material, and to evaluate its potential effect on student learning outcomes. This study employed the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included observation, interviews, validation sheets, questionnaires, and a test consisting of 5 post-test questions. The validity test was conducted by material experts, media experts, language experts, as well as a material expert assessment of the post-test questions. The subjects of this study were 24 students from class XI 5 of SMA N 5 Jambi City. The small group product trial was conducted at the implementation stage with 10 students from class XI 2, while the large group trial was conducted on 24 students from class XI 4. The assessment results showed a percentage of 95.3% for material with a